PUMA gene delivery to synoviocytes reduces inflammation and degeneration of arthritic joints - Saw-See Hong (Nature Portfolio, 2017)
Proliferation of synoviocytes contributes to joint damage in rheumatoid arthritis. Here the authors show that targeting of these cells by a vector, consisting of a baculovirus conjugated to an adenovirus carrying the pro-apoptotic gene PUMA, has therapeutic efficacy in a rat arthritis model.